AB1099 An audit on the screening guidelines for uveitis in children with juvenile idiopathic arthritis within the royal hospital for children, glasgow. (12th June 2018) - Waddell, J.; Parmar, E.; Gardner-Medwin, J.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) defines many arthropathies occurring in children which persist for at least 2 weeks. All JIA patients are at risk of developing uveitis, an inflammatory condition of the eye which poses a risk to visual impairment. The British Society of Paediatric and Adolescent Rheumatology outline guidelines for the screening of these patients. Given the time since publication, an audit on the adherence to said guidelines, as well as patient outcomes, was conducted. Objectives: Our aim was to identify adherence to the screening guidelines within the RHC, Glasgow; and to what extent adherence to these guidelines prevented the occurrence of uveitis. We aimed to identify areas which could be improved within the Glasgow service itself, as well as providing data for the revision of the guidelines. Methods: We performed a clinical audit of all JIA patients diagnosed between 1st January 2008 and 31st December 2017, analysing the frequency and adherence of appointments, as well as medication use. Data was gathered from patient medical files and collected into a database for analysis. Results: 97 of 115 JIA patients entered the screening programme. 72 patients had their initial eye screen within the appointed guidelines of 6 weeks, and 13 of the patients were examined under anaesthetic, with a mean time to examination of 3.31 weeks (0–7.14). 15 patients were seen according to the two-monthly guidelines for the first 6 months of diagnosis. Following this 6 month period, it is suggested patients are screened every three to four-months. 463 out of 641 (72.2%) appointments met this guideline. After stopping immunosuppressive therapy, it is advised to screen at two-monthly intervals. 97 patients were treated with immunosuppressants, with 10 patients stopping whilst still in the screening service. 9 continued to be seen on a three to four-month basis as before, 1 patient was not screened at all, but no patients were screened according to the guidelines. Conclusions: Adherence to the screening service could be improved, with 75% of patients having had their first screen within the guideline criteria, and 72% seen within the guidelines following the initial 6 months. It seems that improvement mainly needs to be focussed on the methods of appointment rearrangement. There is believed to be a 6 month high-risk period of developing uveitis following cessation of immunosuppressants, thus increased screening is suggested. This was not adhered to well in the Glasgow service, but there was no increased risk of uveitis development found, suggesting the need for alteration to the guidelines. References: [1] British Society for Paediatric and Adolescent Rheumatology (2006) Guidelines for Screening for Uveitis in Juvenile Idiopathic Arthritis (JIA), : BSPAR [2] Ross E Petty, Taunton R Southwood, Prudence Manners, John Baum, David N Glass, Jose Goldenberg, et al. International League of Associations for Rheumatology classification of juvenile idiopathic arthritis: second revision, Feb 2004 ed.: The Journal of Rheumatology; 2004 [3] Muthappan, V; Feldman, B H. Juvenile Idiopathic Arthritis: Uveitis. American Academy of Opthalmology 2015 Acknowledgements: Thank you to all the staff of both the ophthalmology and rheumatology departments at the Royal Hospital for Children, Glasgow, for their dedication to this service and cooperation with this audit Disclosure of Interest: None declared